Innovation and Internationalization of Young Entrepreneurial Firms - Lamotte, Olivier; Colovic, Ana (Management international / International Management / Gestiòn Internacional, 2013)
This article investigates the relationship between innovation and internationalization in young entrepreneurial firms. Based on data from the Global Entrepreneurship Monitor and the World Bank for 64 countries during the 2001-2008 period, this study demonstrates that young entrepreneurial firms involved in product and/or process innovation are more likely to be internationalized. Moreover, the results of our study reveal that the impact of innovation is greater for product innovation than for process innovation and for high-income countries than for low- or middle-income countries.